2016
DOI: 10.1680/jgeot.15.p.157
|View full text |Cite
|
Sign up to set email alerts
|

Scour effects onp–ycurves for shallowly embedded piles in sand

Abstract: Soil scour around a shallowly embedded pile can significantly compromise its lateral response, reducing both stiffness and capacity. Estimation of the lateral pile response must take into account both the scour-hole geometry and the overconsolidation effects on the remaining soil. A series of centrifuge model tests with various scour profiles were conducted at a scale of 1:250 to investigate the effects of both local and general scour on the response of a laterally loaded pile. Measured pile moment distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(28 citation statements)
references
References 24 publications
0
27
0
1
Order By: Relevance
“…Over the past few years, the effect of scour on the static response of single piles has gained interest and has been reported by several studies: Lin et al [5] studied the effect of scour on the response of laterally loaded piles considering the change of stress of the remaining sand. Qi et al [6] investigated the effect of local and global scour on the p-y curves of piles in sand using various centrifuge model tests. These studies showed that scour induces changes in the response of laterally loaded piles.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years, the effect of scour on the static response of single piles has gained interest and has been reported by several studies: Lin et al [5] studied the effect of scour on the response of laterally loaded piles considering the change of stress of the remaining sand. Qi et al [6] investigated the effect of local and global scour on the p-y curves of piles in sand using various centrifuge model tests. These studies showed that scour induces changes in the response of laterally loaded piles.…”
Section: Introductionmentioning
confidence: 99%
“…In calculations done according to the model of Lin et al [25], the soil around the scour hole was included for calculation of the soil wedge at failure; therefore, after scour, the decrease of the lateral ultimate soil resistance around the pile was apparently smaller than the values obtained from other p-y curve modification methods. Qi et al [35] used the pile model test to simulate the load-displacement response for the local scour of a monopile and considered that the soil around the scour hole substantially enhanced the ultimate soil resistance per length near the ground surface. This view accorded with the approach of Lin et al [25].…”
Section: Depth (M)mentioning
confidence: 99%
“…已有相关数 值研究和理论分析主要考虑了两方面的效应: 一是冲 刷诱导的上部土体输移会导致剩余土体处于超固结 状态, 从而改变其力学特性 [15] ; 二是冲刷坑几何尺寸 的影响 [16,17] . 最近, Qi等人 [18] 通过离心机试验进行相关 研究, 引入了一种简便的p-y曲线修正方法, 依据冲刷 图 1 (网络版彩图)冲刷对水平承载单桩响应的影响 对模型土体施加重力场的同时保证土体不发生显著的 变形. Karthigeyan等人 [20] 的研究表明当桩基水平位移 较小时, 竖向荷载对桩基的水平承载影响很小.…”
Section: 约束的不同描述 已发展出了一系列不同的计算方法unclassified